Are "obsessive" beliefs specific to OCD?: a comparison across anxiety disorders. - Tolin, D; Worhunsky, P; Maltby, N (2006)
Cognitive models of obsessive-compulsive disorder (OCD) assign a central role to maladaptive beliefs about threat, uncertainty, importance and control of thoughts, responsibility, and perfection. Previous research has demonstrated that such beliefs relate to specific OCD symptoms in a theoretically meaningful way. The aim of the present study was to determine whether these beliefs are endorsed more strongly by OCD patients than by those with other anxiety disorders. Eighty-nine adult OCD patients, 72 anxious control (AC) patients, and 33 nonclinical control (NCC) participants completed a measure of obsessive beliefs as well as measures of depression and trait anxiety. Compared to NCCs and ACs, OCD patients more strongly endorsed beliefs related to threat estimation, tolerance of uncertainty, importance and control of thoughts, and perfectionism, but not inflated responsibility. Using revised, condensed subscales, OCD patients differed from ACs on beliefs about perfectionism and certainty and about importance and control of thoughts, but not on beliefs about threat estimation and inflated responsibility. When controlling for depression and trait anxiety, the OCD and AC group did not differ on most belief domains, except for a belief that it is possible and necessary to control one's thoughts. Results are discussed in light of evolving cognitive-behavioral theories that highlight appraisals of thought control and the use and effectiveness of varying thought control strategies.